Knygos politika demokratinėje visuomenėje: Estijos pavyzdys - Lott, Mare; Möldre, Aile (Knygotyra, 2005)
The article treats the two sides of book policy — prohibitive and creative — using the example of the Republic of Estonia. If the earlier period of book history was dominated by persecution of authors and the prohibition of books, then contemporary democratic societies manifest freedom of expression, stimulating the dissemination of the most diverse ideas. Freedom of expression, however, does not exist without limits. In the Republic of Estonia in 1918-1940, a special law on the press (1923) introduced post-publication censorship, aimed at the protection of morality. Several books were banned and confiscated on the basis of this law. The other rationale for prohibiting books was the protection of national security, which led to the prohibition of some political publications. In contemporary Estonia, the limitations to freedom of expression entail, like in pre-war Estonia, the protection of public order and morals, but also the rights, freedom, health, honor, and good name of other people. The criminal code prohibits the inciting of national, racial, religious, or political hatred, or propagating violence and disseminating pornography among minors. The freedom to publish all kinds of publications has not been abused to a great extent by publishing dubious publications in Estonia since 1991. The case of publishing "The Protocols of the Elders of Zion" in 1993 caused a discussion about the boundaries of freedom of expression. It was generally agreed that though controversial texts could be accessible to readers, they should be issued with commentaries explaining their origin. The other side of book policy concentrates on fostering the production and distribution of books. The realization of this idea in Estonia dates back to the 1920s when the Cultural Endowment was founded in 1925. The main source of income of the Endowment was the 2.5 percent allocation from the state alcohol excise. The subsidies by the Endowment became the main channel through which the state could influence the development of culture. It preferred to subsidize creative and academic societies that played an important role in publishing scholarly and popular-science publications. The writers were supported through a system of prizes for the books already published—another instrument for fostering works that were in accordance with the official cultural policy. The Endowment had a major role in guaranteeing the high level and diversity of book production in Estonia in the 1920s-1930s. After the restoration of independence in Estonia in 1991, subventions for books have been allocated through the Ministry of Culture. Besides that, the Cultural Endowment was restored in 1995. It subsidizes, above all, the publications of contemporary Estonian fiction and publications on art and culture. In comparison with the pre-war years, the authors and publishers are granted allocations on a larger scale, and the share of scholarly societies is more modest. The issuing of research results is mainly supported through the grants of the Estonian Science Foundation. The restoration of the Endowment remains the greatest achievement in stimulating book production in Estonia. The other measures of national book policy have been less clear and effective.